Assessment of soil fraction, carbon storage capacity, and rate of carbon uptake from three coastal ecosystems: Mangroves, seagrass, and mudflats in Benoa Bay, Indonesia - I GUSTI NGURAH PUTU DHARMAYASA; I PUTU SUGIANA; PUTU YUDI ADITYA PUTRI; KWANRUETAI BOONYASANA (Society for Indonesian Biodiversity, 2024)
Abstract. Dharmayasa IGNP, Sugiana IP, Putri PYA, Boonyasana K. 2024. Assessment of soil fraction, carbon storage capacity, and rate of carbon uptake from three coastal ecosystems: Mangroves, seagrass, and mudflats in Benoa Bay, Indonesia. Biodiversitas 25: 2541-2549. Coastal habitats, known as blue carbon ecosystems, are highly productive at absorbing and storing carbon. Most carbon is stored as soil organic carbon, and its quantity can vary depending on various factors, including the presence of plants such as mangroves and seagrass, and environmental conditions, including soil fraction. This study quantifies soil carbon stored and its burial rate in three primary coastal ecosystems: mangroves, seagrasses, and mudflats. The ashing method (loss on ignition) is used to quantify carbon content, which is then converted into soil carbon storage and burial rate. Gravimetry and the settling time method are used to determine the soil fraction. We also measure the soil and water properties directly during the sampling time. This study revealed significant soil carbon stock and burial rate variations across different ecosystems. The order of ecosystems with the most extensive carbon stock and burial rate is as follows: mangrove (69-145 tC ha-1 and 1.6-3.4 tCha-1yr-1)>seagrass (63-75 tC ha-1 and 1.5-1.7 tCha-1yr-1)>mudflat (49-61 tC ha-1 and 1.2-1.4 tCha-1yr-1). Mangroves with natural growth have a higher carbon storage capacity than rehabilitated ones. Soil carbon content is highly correlated with the soil and water pH, Dissolved Oxygen (DO), water content, bulk density, and soil type. The findings demonstrate that carbon absorption capability varies among coastal habitats, with vegetated environments exhibiting higher carbon storage levels. Converting land, particularly mudflats, into seagrass beds or mangrove forests may maximize the efficiency of coastal ecosystems as carbon sinks. However, it should be noted that these findings are only estimates, and the precise measurement numbers may differ due to seasonal circumstances or reclamation activities, which might cause oscillations in sedimentation rates. These variations, in turn, could affect the levels of carbon stored and the speed at which it is buried.